2018
DOI: 10.1186/s12868-018-0469-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the neurotransmitter profile of AmFoxP expressing neurons in the honeybee brain using double-label in situ hybridization

Abstract: BackgroundFoxP transcription factors play crucial roles for the development and function of vertebrate brains. In humans the neurally expressed FOXPs, FOXP1, FOXP2, and FOXP4 are implicated in cognition, including language. Neural FoxP expression is specific to particular brain regions but FoxP1, FoxP2 and FoxP4 are not limited to a particular neuron or neurotransmitter type. Motor- or sensory activity can regulate FoxP2 expression, e.g. in the striatal nucleus Area X of songbirds and in the auditory thalamus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 170 publications
3
0
0
Order By: Relevance
“…Finally, a few FoxP-iB positive neurons were found to colocalize with tyrosine hydroxylase (dopaminergic neurons) in the CB only ( figure 3 d ). These data are consistent with the study performed by Schatton et al [ 37 ] in honeybees where they found colocalization between AmFoxP-positive neurons and GABAergic, cholinergic and monoaminergic markers. No colocalization was instead found in photoreceptor cells stained with Chaoptin (data deposited at doi:10.6084/m9.figshare.12607643 10.6084/m9.figshare.12607643 ), a marker for photoreceptor cells [ 38 ].…”
Section: Resultssupporting
confidence: 93%
“…Finally, a few FoxP-iB positive neurons were found to colocalize with tyrosine hydroxylase (dopaminergic neurons) in the CB only ( figure 3 d ). These data are consistent with the study performed by Schatton et al [ 37 ] in honeybees where they found colocalization between AmFoxP-positive neurons and GABAergic, cholinergic and monoaminergic markers. No colocalization was instead found in photoreceptor cells stained with Chaoptin (data deposited at doi:10.6084/m9.figshare.12607643 10.6084/m9.figshare.12607643 ), a marker for photoreceptor cells [ 38 ].…”
Section: Resultssupporting
confidence: 93%
“…3D). These data are consistent with the study performed by [36] in honeybees where they found colocalization between Am-FoxP positive neurons and GABAergic, cholinergic and monoaminergic markers. No colocalization was instead found in photoreceptor cells stained with Chaoptin (data deposited at doi: 10.6084/m9.figshare.12607643), a marker for photoreceptor cells [37].…”
Section: Resultssupporting
confidence: 93%
“…3D). These data are consistent with the study performed by (Schatton et al, 2018) (Pollock et al, 1990). 4E).…”
Section: Foxp-ib Expression In the Drosophila Brainsupporting
confidence: 93%